What Are the Double Lines of the Fetal Cavum Septi Pellucidi on Ultrasound?. (9th November 2021) - Green, Shannon; Pretorius, Dolores H.; Crouch, Amanda; Anton, Tracy; Jacobs, Marni; Ho, Yoona; Hevner, Robert; Lamale‐Smith, Leah
Abstract : Objective: To demonstrate the significance of the double line appearance of the septi pellucidi laminae (SPL) on fetal ultrasound. Method: A total of 522 uncomplicated singleton pregnancies (15 to 39 weeks' gestational age) with fetal ultrasounds were enrolled. The presence of a single versus double line SP as well as measurement of the cavum septi pellucidi (CSP) was determined retrospectively. Ultrasound settings from the CSP images were recorded. Thickness of the SPL was measured in 20 ultrasound and 14 MRI cases; histology was reviewed from one neonate. Maternal BMI and gestational age were also recorded. Results: The presence of double line SPL is a normal sonographic finding, seen in 47% (188/403) of normal fetuses. Thickness of the SPL in 10 cases with double line averaged 1.4 mm and in 10 cases with single line averaged 0.8 mm; MRI measurements were within 0.1 mm of the corresponding ultrasound measurements. Double line cavum was more often seen with mid‐dynamic contrast range settings (5, 6) rather than high range settings (7–10) ( P value <.05). The double line was only visualized on ultrasound when the angle of insonation was at or near perpendicular to the laminae; it was never visualized on coronal ultrasound imaging or MRI imaging. Conclusion: A double line septum pellucidum lamina is a normal finding seen in almost 50% of uncomplicated singleton pregnancies. It may be attributed to borders of cell layers within each lamina that form separate specular reflections on both sides; this can be accentuated by ultrasound settings and beam angulation.